Audio Visual Material for Safety Briefing Learning for Students in School Laboratories - Wina Puspita Sari; Asep Soegiarto; Muria Putriana (STAI Hubbulwathan Duri, 2024)
This study aims to explore the perceptions of students and teachers regarding the effectiveness of audio-visual teaching materials in enhancing the understanding of occupational health and safety in school laboratories. The study employs a qualitative approach, utilizing descriptive methods to gather and analyze data. The research was carried out at Al-Ittihad Cianjur Vocational School, a technical and vocational education institution. The informants for this research were the Head of the Laboratory Program, the Person in Charge of the Laboratory, the School Principal, 7 teachers who taught in the laboratory, and 100 students. Data were collected through various techniques, including observations, document analysis, interviews, and focus group discussions (FGDs). To determine the level of reliability or trustworthiness of data, this research uses credibility, transferability, dependability, and confirmability. The data analysis technique uses qualitative data which includes stages of data reduction, data presentation, and conclusion. The research results concluded that the provision of audio-visual teaching materials in the form of videos was very good and had a positive impact on learning. The students have quite good attitudes when carrying out learning activities, especially regarding their work safety in the laboratory. These findings also provide awareness about the importance of increasing digital competence so that teachers can be more creative and innovative in creating learning resources.